Pengaruh Kebijakan Harga dan Kualitas Produk Terhadap Loyalitas Pelanggan pada Produk Kesehatan Hewan - Octriliani Octriliani; Halimah Zahrah; Indra Sasangka (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The pet care or pet shop industry in Indonesia is currently experiencing significant growth in line with increasing public awareness and the tendency to keep pets and consider them part of the family (pets as family), a phenomenon known as the pet economy. This is also accompanied by increased attention to the health and welfare of pets. This situation makes product quality the main foundation for building customer loyalty, as pet owners are becoming more critical and knowledgeable, seeking not only feed or care products but also the best products for the health and welfare of their beloved pets. This study aims to determine the extent of the influence of Clean'Nest's pricing policy and product quality on consumer loyalty at PT Hollycat Summarecon Bandung using a quantitative approach through a survey method of 32 customers selected using purposive sampling. Data collection was carried out using a 1–5 Likert scale questionnaire that had been tested for validity and reliability, and analyzed using multiple linear regression with the help of SPSS version 26. The results of the study indicate that simultaneously, pricing policy (X1) and product quality (X2) influence customer loyalty, but partially, only product quality has a significant effect, while pricing policy does not, with a coefficient of determination of 79.1%.